2014
DOI: 10.5812/ircmj.11195
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-Alpha Polymorphism at Position -238 in Preeclampsia

Abstract: Background:Preeclampsia is the most common serious disorder during pregnancy and studies show several immune-related processes in its pathophysiology. The role of cytokines and their expression remains controversial in this field. One of the cytokines of interest in recent studies has been TNF-α, which has been shown to have a higher level in maternal plasma of preeclamptic women.Objectives:This study was designed to evaluate the role of TNF-α polymorphism at position -238 in the risk of developing preeclampsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
0
18
1
Order By: Relevance
“…As PE is a polygenetic hereditary disease and previous studies have been indicated that many cytokine genes are associated with susceptibility to it such as VEGF [35,36], NLRP1 [37], IL-1 [15,16], TNF-α [17,18], IFN-γ [19] and so on. Therefore in the present study we investigated whether IL-33 rs3939286 and IL-1RL1 rs13015714 play pivotal roles in the development of PE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As PE is a polygenetic hereditary disease and previous studies have been indicated that many cytokine genes are associated with susceptibility to it such as VEGF [35,36], NLRP1 [37], IL-1 [15,16], TNF-α [17,18], IFN-γ [19] and so on. Therefore in the present study we investigated whether IL-33 rs3939286 and IL-1RL1 rs13015714 play pivotal roles in the development of PE.…”
Section: Discussionmentioning
confidence: 99%
“…PE is a complex polygenetic hereditary disease involving both genetic and environmental factors [14] and previous studies have identified many candidate genes associated with susceptibility to it, such as IL-1 [15,16], TNF-α [17,18], IFN-γ [19] and so on. We therefore hypothesize that IL-33 and IL-1RL1 might play critical roles in pathophysiology of PE.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these factors lead to vasoconstriction, which can result in the occurrence of hypertension (high blood pressure) involved in preeclampsia (20,21). A study conducted by Farzadnia et al in Mashhad University of Medical Sciences on the genotypes of patients showed that the frequency of AA was significantly higher than GG in patients with preeclampsia (22). Moreover, a study conducted on the mouse cremaster muscle suggested that TNF-α protein resulted in protein leakage from small blood vessels (23).…”
Section: Immune System and Preeclampsiamentioning
confidence: 99%
“…TNF‐α polymorphisms at −308 and at −238 are associated with increased incidence of unstable angina and preeclampsia respectively. IL‐6 polymorphism C/G at −174 can predict risk for cardiovascular events …”
Section: Introductionmentioning
confidence: 99%